2002
DOI: 10.1253/circj.66.841
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Endothelin AB Antagonist on Sympathetic Outflow in Conscious Rats With Heart Failure.

Abstract: ndothelin (ET) is a vasoconstrictor peptide thatgreatly increases the contractility of vascular smooth muscle in pathological and physiological states. 1,2 Recent studies have shown that myocardial and plasma ET concentrations are elevated in congestive heart failure (HF), and increased endogenous ET plays a role in the progression of HF by induction of hypertrophy in cardiomyocytes and left ventricular dilatation. 3 Furthermore, long-term inhibition by the administration of ET A and AB receptor antagonist imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Bosentan treatment caused a marked decrease in cardiac baroreflex sensitivity and this indicates the important contribution of ET‐1 in the autonomic reflex control of HR. This contribution had already been suggested by previous studies, 14–21 even though the effects of ET on autonomic reflex control were divergent. A possible explanation for these divergent findings is the different site of actions of ET within the baroreflex arc of cardiovascular control.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Bosentan treatment caused a marked decrease in cardiac baroreflex sensitivity and this indicates the important contribution of ET‐1 in the autonomic reflex control of HR. This contribution had already been suggested by previous studies, 14–21 even though the effects of ET on autonomic reflex control were divergent. A possible explanation for these divergent findings is the different site of actions of ET within the baroreflex arc of cardiovascular control.…”
Section: Discussionsupporting
confidence: 72%
“…In anaesthetized rats, injection of low doses of ET‐1 into the cisterna magna increases renal sympathetic nerve activity (RSNA), HR and arterial pressure, but injection of high doses of ET‐1 has the opposite effect 15 . Conversely, acute and systemic blockade of ET‐1 receptors with the non‐selective antagonist TAK044 causes a decrease in RSNA in rats with cardiac failure 20 . A further study has shown that bolus injection of bosentan does not alter the sympathetic–vagal balance in rats with renal denervation or in sham‐operated rats 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of the ET-1 receptor in dogs with pacing-induced HF reduced plasma NE levels compared with placebo infusion (21). Interestingly, infusion of an ET-1 receptor antagonist reduced directly recorded renal sympathetic nerve activity (RSNA) in pacing-induced HF in rabbits (16) and in the myocardial infarction model of HF in rats (38).…”
Section: Discussionmentioning
confidence: 99%